Heavy‐Atom‐Free Bay‐Substituted Perylene Diimide Donor‐Acceptor Photosensitizers. Issue 14 (15th June 2021) - Deckers, Jasper; Cardeynaels, Tom; Lutsen, Laurence; Champagne, Benoît; Maes, Wouter
Abstract: Perylene diimide (PDI) dyes are extensively investigated because of their favorable photophysical characteristics for a wide range of organic material applications. Fine‐tuning of the optoelectronic properties is readily achieved by functionalization of the electron‐deficient PDI scaffold. Here, we present four new donor‐acceptor type dyads, wherein the electron donor units – benzo[1, 2‐ b : 4, 5‐ b' ]dithiophene, 9, 9‐dimethyl‐9, 10‐dihydroacridine, dithieno[3, 2‐ b : 2', 3'‐ d ]pyrrole, and triphenylamine‐are attached to the bay‐positions of the PDI acceptor. Intersystem crossing occurs for these systems upon photoexcitation, without the aid of heavy atoms, resulting in singlet oxygen quantum yields up to 80 % in toluene solution. Furthermore, this feature is retained when the system is directly irradiated with energy corresponding to the intramolecular charge‐transfer absorption band (at 639 nm). Geometrical optimization and (time‐dependent) density functional theory calculations afford more insights into the requirements for intersystem crossing such as spin‐orbit coupling, dihedral angles, the involvement of charge‐transfer states, and energy level alignment. Abstract : Intersystem crossing in PDIs ? N, N'‐substituted perylene diimides (PDIs), functionalized at the bay‐positions with different donor moieties, were synthesized and characterized. Despite non‐orthogonal donor‐acceptor orientation, triplet formation was observed, both upon direct excitation in the localized perylene and the charge‐transfer absorption band. Time‐dependent density functional theory analysis provided further insights into the involved intersystem crossing features.